2005
DOI: 10.1128/cdli.12.8.941-948.2005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Significance of Immunoglobulin A Antibodies against Tissue Transglutaminase in Patients with Diverse Chronic Liver Diseases

Abstract: The prevalence of celiac disease (CD) and the prevalence and clinical significance of anti-tissue transglutaminase (tTG) antibodies (tTGAbs) in a large series of patients with chronic liver diseases were assessed. We studied 738 patients (462 with chronic viral hepatitis, 117 with autoimmune liver diseases, 113 with alcoholic or nonalcoholic fatty liver disease, and 46 with other liver disorders) and 1,350 healthy controls (HC). Immunoglobulin A (IgA) tTGAbs were measured by enzyme-linked immunosorbent assay a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1
9

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 52 publications
0
23
1
9
Order By: Relevance
“…In our literature review, we found four prospectively designed screening studies (Table 3); of these, three had a normal control group [17,24,25]. The pooled population of HCV was 1,072 patients; of these, a total of 14 patients were positive for celiac disease.…”
Section: Discussionmentioning
confidence: 99%
“…In our literature review, we found four prospectively designed screening studies (Table 3); of these, three had a normal control group [17,24,25]. The pooled population of HCV was 1,072 patients; of these, a total of 14 patients were positive for celiac disease.…”
Section: Discussionmentioning
confidence: 99%
“…HLA typing was also limited. Additionally, the presence of neurological dysfunction was not examined[46]. …”
Section: Discussionmentioning
confidence: 99%
“…SB villus changes and atrophy are characteristic, but are not specific for coeliac disease [24,25] . Coeliac serological tests have low sensitivities and specificities in chronic liver disease and cirrhosis [15,[26][27][28][29] which emphasizes the importance of validating SB biopsy as the most important tool for the diagnosis of CD in this group of patients. Results of this study support the use of SB biopsy in patients with cirrhosis and portal hypertension when the diagnosis of CD is suspected.…”
Section: Discussionmentioning
confidence: 99%
“…This is in part due to the heightened awareness of the association of CD with a variety of liver disorders. Most commonly described associated liver disorders include autoimmune hepatitis, primary biliary cirrhosis, non-alcoholic fatty liver disease, unexplained abnormal liver tests and cirrhosis [8][9][10][11][12][13][14][15] . The mechanisms of this association are not clear and the prevalence of CD in patients with liver disease is variable depending on the associated liver disease.…”
Section: Introductionmentioning
confidence: 99%